Phase Variable Expression of Capsular Polysaccharide Modifications Allows Campylobacter jejuni to Avoid Bacteriophage Infection in Chickens - Sørensen, Martine C.; van Alphen, Lieke B.; Frodor, Christopher; Crowley, Shauna; Christensen, Bjarke B.; Szymanski, Christine M.; Brøndsted, Lone (Frontiers in Cellular and Infection Microbiology, 2012)
Bacteriophages are estimated to be the most abundant entities on earth and can be found in every niche where their bacterial hosts reside. The initial interaction between phages and Campylobacter jejuni, a common coloniser of poultry intestines and a major source of foodborne bacterial gastroenteritis in humans, is not well understood. Recently, we isolated and characterised a phage F336 resistant variant of C. jejuni NCTC11168 called 11168R. Comparisons of 11168R with the wildtype lead to the identification of a novel phage receptor, the phase variable O-methyl phosphoramidate (MeOPN) moiety of the C. jejuni capsular polysaccharide (CPS). In this study we demonstrate that the 11168R strain has gained cross-resistance to four other phages in our collection (F198, F287, F303 and F326). The reduced plaquing efficiencies suggested that MeOPN is recognized as a receptor by several phages infecting C. jejuni. To further explore the role of CPS modifications in C. jejuni phage recognition and infectivity, we tested the ability of F198, F287, F303, F326 and F336 to infect different CPS variants of NCTC11168, including defined CPS mutants. These strains were characterised by high-resolution magic angle spinning NMR spectroscopy. We found that in addition to MeOPN, the phase variable 3-O-Me and 6-O-Me groups of the NCTC11168 CPS structure may influence the plaquing efficiencies of the phages. Furthermore, co-infection of chickens with both C. jejuni NCTC11168 and phage F336 resulted in selection of resistant C. jejuni bacteria, which either lack MeOPN or gain 6-O-Me groups on their surface, demonstrating that resistance can be acquired in vivo. In summary, we have shown that phase variable CPS structures modulate phage infectivity in C. jejuni and suggest that the constant phage predation in the avian gut selects for changes in these structures leading to a continuing phage-host co-evolution.